The association of Th17/Treg cells expression in peripheral blood and chronic spontaneous urticaria: A protocol of systematic review and meta-analysis - Yu, Qianying (Medicine (Baltimore), 2020)
BACKGROUND: The pathogenesis of chronic spontaneous urticaria (CSU) is not clear, but its occurrence is closely related to the immune state of the body, that is, the balance of T cell subsets. Previous studies have confirmed that the dynamic imbalance of Th1/Th2 cells in CD4+T cell subsets of T cell subsets is closely related to the pathogenesis of CSU, but there are few studies on the relationship between the dynamic imbalance of Th17/Treg cells in CD4+T cell subsets and the pathogenesis of CSU. The purpose of this study is to evaluate the relationship between Th17/Treg cells expression in peripheral blood and CSU, so as to provide a reference basis for the pathogenesis of CSU. METHODS: PubMed, Embase, CENTRAL, Web of Science, China Biology Medicine Database, China National Knowledge Database, Wan Fang Database, and Chongqing VIP Database will be searched to collect case-control studies and cohort studies evaluating the relationship between Th17/Treg cells expression in peripheral blood and CSU. The search time limits will be from the establishment of the database to December 2020. The meta-analysis will be carried out with the RevMan V.5.3 statistical software. The quality of all included studies will be evaluated by the Newcastle-Ottawa scale. RESULTS: The results of this study will comprehensively evaluate the Th17/Treg cells expression levels in peripheral blood of patients with CSU, and provide a reference basis for the pathogenesis of CSU. CONCLUSION: The findings of this study may provide new evidence for the relationship between Th17/Treg cells balance in peripheral blood and CSU. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/S8MYW